2022
DOI: 10.21203/rs.3.rs-1858867/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subjective socioeconomic status: an alternative to objective socioeconomic status

Abstract: Background Subjective “ladder” measurements of socio-economic status (SES) are easy-to-administer tools that ask respondents to rate their own SES, allowing them to evaluate where they believe their material resources place them relative to their community. Here, we sought to compare a ladder score to a measure of SES that includes data on water and sanitation, asset ownership, education, and income (WAMI). Methods Leveraging an ongoing study of adult patients with tuberculosis in Lima, Peru, we compared res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The data collection tool consisted of characteristics. Subjective "scale" measures of socioeconomic status (SES) are easy-to-administer instruments that ask respondents to rate their own SES, allowing them to assess their material resources (10). The MacArthur Scale was used to measure the SES of candidates during childhood (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data collection tool consisted of characteristics. Subjective "scale" measures of socioeconomic status (SES) are easy-to-administer instruments that ask respondents to rate their own SES, allowing them to assess their material resources (10). The MacArthur Scale was used to measure the SES of candidates during childhood (8).…”
Section: Methodsmentioning
confidence: 99%
“…The lowest level is denoted by the first number (19), while the highest number is represented by the 10th number. Scholars have revealed that a rating scale is more effective in showing the relationship between individual mental health and SES than traditional objective indicators (10,20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The superiority of subjective measures over objective measures of socioeconomic status may stem from their ability to offer a more comprehensive evaluation. While objective measures provide a snapshot of present resources, subjective indicators offer a more holistic assessment that accounts for historical and current outcomes, alongside future prospects in light of individuals’ social and cultural environment (Zhao et al, 2023). Hence, in the current research, we will focus on subjective socioeconomic status.…”
Section: Socioeconomic Status Sense Of Belonging and Academic Achieve...mentioning
confidence: 99%